Popliteal artery thrombosis as a rare complication of paroxysmal nocturnal hemoglobinuria (PNH): A case report. (October 2021) - Bhusal, Kiran; Kadel, Prashiddha B.; Bhandari, Khagendra; Aryal, Shova; Gyawali, Nitin; Kushwaha, Ashok; Shrestha, Kajan Raj; Shrestha, Anjan
Abstract: Introduction and importance: Popliteal artery thrombosis a rare but life-threatening complication of Paroxysmal Nocturnal Hemoglobinuria caused due to hemolysis. Complications of further thrombotic event are common after initial management. Case presentation: A 38 years old male, known case of PNH for 2 years, presented with the history of loss of pain sensation, coldness and loss of movement in left lower leg for 5 days and history of multiple blood transfusion. The patient underwent knee amputation because of possible complication of PNH. Clinical discussion: Intermittent claudication along with paresthesia, lower extremity weakness, stiffness, and cool extremities are seen in patients of Peripheral Artery Disease. Ultrasound color duplex is a sensitive and specific examination for peripheral flow while gold standard techniques like MRI and CT angiogram to detect and diagnose arterial lesions. Conclusion: The risk of thrombo-embolism in a patient of PNH should be considered by a treating doctor while early imaging and management should be done to reduce the complications and risk of amputation. Highlights: Popliteal artery thrombosis is a rare life-threatening complication of Paroxysmal nocturnal hemoglobinuria (PNH) We report a known case of PNH patient diagnosed with acute occlusion of Popliteal artery due to thrombosis. Complications of further thrombotic event are common after initial management and subsequent above knee amputation was done.